Carefulness Matters: Consumer Responses to Short Message Service Advertising. Issue 4 (1st October 2016) - Tseng, Fan-Chen; Teng, Ching-I
ABSTRACT: Short message service (SMS) has been widely used by consumers, and SMS advertising has emerged as a popular topic in advertising and mobile commerce areas. However, the literature has not sufficiently clarified the impact of consumers' carefulness in reading SMS ad messages (the extent to which a consumer reads an ad thoroughly and thoughtfully) on their responses. Using the SMS reading behavior and the SMS advertising effectiveness models as overarching frameworks, this study developed a research model explaining the effect of consumers' carefulness in reading SMS ad messages on their responses. The findings of this study indicate that if consumers give their explicit permission to receive SMS ad messages from a company, they are more likely to read such messages carefully, which further strengthens the effects of the messages' content relevance, informativeness, entertainment, and interactivity on their attitudes toward the received messages. This study is new in introducing reading carefulness to explain consumers' responses to SMS advertising. Moreover, it initiated the inclusion of two novel responses, that is, intention to forward SMS ad messages and intention to contact marketers for more information. The findings provide useful and practicable insights to marketers for effectively communicating with consumers via SMS.